1992
DOI: 10.1007/bf01309653
|View full text |Cite
|
Sign up to set email alerts
|

Replicative difference in early-passage feline brain cells among feline immunodeficiency virus isolates

Abstract: The susceptibility of early-passage feline brain cells and Crandell feline kidney (CRFK) cells to infection with three isolates of feline immunodeficiency virus (FIV) was investigated. The Petaluma strain of FIV could well infect both the feline brain cells and CRFK cells. The KYO-1 strain could well infect the feline brain cells but the replication in CRFK cells was demonstrated only by coculturing fresh feline T-lymphoblastoid cells with the infected cells. On the other hand, the TM1 strain could infect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…HIV-1 strains show various cell tropisms, and most isolates of HIV-1 infect CD 4-positive cells [8,9], but certain isolates can infect CD 4-negative cells such as glial cells [7,34] and fibroblasts [28]. Recently, different cell tropisms among FIV isolates in vitro were reported [14]. The FIV strains used in this study showed some variation in host cell range; while Petaluma and KYO-1 strains infected CRFK cells and fetal feline brain cells, TM 1 IC did not infect these cells and seems to be highly T lymphotropic.…”
Section: Discussionmentioning
confidence: 98%
“…HIV-1 strains show various cell tropisms, and most isolates of HIV-1 infect CD 4-positive cells [8,9], but certain isolates can infect CD 4-negative cells such as glial cells [7,34] and fibroblasts [28]. Recently, different cell tropisms among FIV isolates in vitro were reported [14]. The FIV strains used in this study showed some variation in host cell range; while Petaluma and KYO-1 strains infected CRFK cells and fetal feline brain cells, TM 1 IC did not infect these cells and seems to be highly T lymphotropic.…”
Section: Discussionmentioning
confidence: 98%
“…Different FIV isolates may differ in their in vitro host range even with respect to cells apparently showing the same surface phenotype (100,178,232). The reasons are not known but might involve differences in the Env protein as well as in the composition of the proviral LTR.…”
Section: Replication and Effects On Cells In Vitromentioning
confidence: 99%
“…Early studies on FIV tropism demonstrated that virus could be recovered from brain and CSF of infected cats (Dow et al 1990;Macchi et al 1998;Power et al 1997). In vitro studies of CNS cell tropism indicate that FIV can infect feline astrocytes Danave et al 1994;Dow et al 1990;Kawaguchi et al 1992;Yu et al 1998), microglia (Dow et al 1990;Hein et al 2000;Kawaguchi et al 1992), choroid plexus macrophages (Bragg et al 2002a), and perhaps brain microvascular endothelial cells (Steffan et al 1994). In vivo studies indicate that most virus production in the CNS is maintained by macrophages and microglia Hein et al 2000).…”
Section: Fiv Neurotropism and Neuropathogenesis Fiv Neurotropismmentioning
confidence: 99%